Board chairmen’s involvement in the nomination and remuneration committees and earnings management - Al-Absy, Mujeeb Saif Mohsen; Ku Ismail, Ku Nor Izah; Chandren, Sitraselvi (2018)
The attention given by regulators, investors and financial community to the issue of financial scandals has increased over the past decades (Bowen, Freidank, Wannow, & Cavallone, 2017). Among the reasons for these scandals is earnings management (EM), where experience has shown that companies that engage in EM (e.g., creative accounting), often end up committing fraud (Jones, 2011). Basically, EM is an accounting treatment to alter the earnings result in the financial statements (Chandren, 2016; Chandren, Ahmad, & Ali, 2015), either by using the accrual earnings management (AEM) or real earnings management (REM) (Chandren, Ahmad, & Ali, 2017). Therefore, the occurrence of EM practice motivates managers to commit fraud in the future rather than EM (Perols & Lougee, 2011; Sulaiman, Danbatta, & Rahman, 2014). More importantly, the EM problem is not new (Levitt, 1998); it has however increased due to the market growth that is challenging for companies that do not meet investors’ expectations (Dechow, Sloan, & Sweeney, 1996; Levitt, 1998). Thus, managers become more likely to report opportunistically to match peer performance (Du & Shen, 2018).